Development induced Displacement (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
To every political policy, economic and development project on the one side there is welfare in terms of benefits reaped by some section of population and on the other side it increases sorrows and despair to others. Each year, millions of people around the globe are relocated and resettled away from their homes, lands and livelihoods in order to make way for large-scale development projects such as dams, reservoirs, power plants, roads, plantations, urban renewal, and oil, gas, and mining projects. This forced relocation is known as development-induced displacement. Development has uprooted people not only from homes, but homelands to which they may have been tied by old ancestral bonds. Displacement deprives people from many things, some of them are fundamental to their lives, including homes, productive assets, culture, livelihoods, environmental conditions suited to their skill and practices, community networks and sense of belonging. The determination of the extant of deprivation, plight and sufferings depends on what they face at new location and resource they enjoy there. If proper compensation is being provided in terms of economic incentives and rehabilitation then both the developmental project and displacement can be justifiable. The paper will provide an overview about development induced displacement cases, how many people it affects, what are primary causes and main impacts. It will also highlight certain recommendatory measures for sustainable development and welfare oriented development enjoyed by all in equal sense.